2016
DOI: 10.1371/journal.pone.0148760
|View full text |Cite
|
Sign up to set email alerts
|

Improved Resection and Outcome of Colon-Cancer Liver Metastasis with Fluorescence-Guided Surgery Using In Situ GFP Labeling with a Telomerase-Dependent Adenovirus in an Orthotopic Mouse Model

Abstract: Fluorescence-guided surgery (FGS) of cancer is an area of intense development. In the present report, we demonstrate that the telomerase-dependent green fluorescent protein (GFP)-containing adenovirus OBP-401 could label colon-cancer liver metastasis in situ in an orthotopic mouse model enabling successful FGS. OBP-401-GFP-labeled liver metastasis resulted in complete resection with FGS, in contrast, conventional bright-light surgery (BLS) did not result in complete resection of the metastasis. OBP-401-FGS red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…We have previously demonstrated OBP-401-based fluorescence-guided surgery is highly effective in various types of cancers including soft tissue sarcoma [4], glioblastoma [5], pancreatic cancer [6], lung cancer [7], colon cancer-liver metastasis [8], and melanoma [9]. In contrast, conventional bright-light surgery (BLS) could not fully resect these tumors [49].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated OBP-401-based fluorescence-guided surgery is highly effective in various types of cancers including soft tissue sarcoma [4], glioblastoma [5], pancreatic cancer [6], lung cancer [7], colon cancer-liver metastasis [8], and melanoma [9]. In contrast, conventional bright-light surgery (BLS) could not fully resect these tumors [49].…”
Section: Introductionmentioning
confidence: 99%
“…We have developed an orthotopic colon-cancer liver metastasis model and have shown improved outcomes after resection using fluorescence labeling (14). Colon cancer liver metastases were modeled by serially selecting for aggressive liver metastasis variants of colon cancer cells after splenic injection.…”
mentioning
confidence: 99%
“…Tumor-specific fluorescence was delivered in situ via viral vector expressing green fluorescent protein (GFP) or a fluorescently labeled antibody. Yano et al and Kishimoto et al used OBP-401, a conditionally replicative adenovirus with the replication cassette under the control of the human telomerase reverse transcriptase (hTERT) promoter and a GFP tag under the control of a cytomegalovirus (CMV) promoter (14,15). Three days after direct intratumoral injection of the adenovirus, a strong GFP signal was present at the tumor site and the fluorescence signal was used for fluorescenceguided surgery (FGS).…”
mentioning
confidence: 99%
“…Our lab has shown that the use of tumor-specific fluorescent organ labeling in laparoscopy aids in rapid and accurate identification of tumors, especially at the sub-millimeter resolution (16). We have also studied FGS with tumor-specific fluorescence in a colon-cancer liver-metastasis model (17,18). Fluorescence was delivered via an anti-CEA antibody or tumor-specific adenovirus vectors expressing GFP.…”
mentioning
confidence: 99%